Chitosan-polyglycidol complexes to coating iron oxide particles for dye adsorption. (15th October 2020) - Iovescu, Alina; Stîngă, Gabriela; Maxim, Monica Elisabeta; Gosecka, Monika; Basinska, Teresa; Slomkowski, Stanislaw; Angelescu, Daniel; Petrescu, Simona; Stănică, Nicolae; Băran, Adriana; Anghel, Dan-Florin
Graphical abstract: Highlights: Interaction among chitosan (Ch) and polyglycidol (PGL) is studied in aqueous media. Molecular dynamics simulations show that Ch and PGL form weak strength complexes (C). Complex C is used in alternation with SDS (S) to cover iron oxide particles (M). Hydrophilic multilayer deposition is proved by DLS, Z potential, FTIR, EDAX. The novel magnetic material (MSCS) efficiently captured methylene blue from water. Abstract: The study sheds light on the interaction between chitosan (Ch) and polyglycidol (PGL) and uses their interpolymer complex in hydrophilic coating of iron oxide particles (M). Preliminary investigations were performed by modeling chitosan and polyglycidol chains interactions using coarse grained beads approximation and molecular dynamics simulations. The results revealed that Ch and PGL chains associate together forming weak strength complexes, which was experimentally confirmed by surface tension, fluorescence and FTIR. The Ch-PGL mixture (C) and sodium dodecylsulfate (S) were used for layer-by-layer preparation of hydrophilic multilayer coatings of M. The successful covering, demonstrated by DLS, Zeta potential, FTIR, EDAX, preserved the particles super-paramagnetic properties. The most stable multilayer nanocomposite (MSCS) efficiently adsorbed methylene blue from water. The Freundlich model fitted well the equilibrium isotherm data, indicating a heterogeneous, multilayer adsorption. Benefiting from both nano-size and magnetic properties, this adsorbent could be an effectively, cheaply and eco-friendly wastewater treatment means.